Rationale and Study Design for Evaluating the Efficacy and Safety of Intracardiac Echocardiography-Guided Minimal-Fluoroscopy Ablation in Patients with Paroxysmal Atrial Fibrillation: A Non-Inferior, Multi-Center, Prospective Randomized Controlled Trial (PAF-ICE Trial). Issue 4 (13th December 2021) - Jiang, Ruhong; Liu, Xingpeng; Zhang, Jidong; Chen, Yu; Wang, Rui; Wu, Mengzuo; Long, Deyong; Li, Jia; Wang, Haixiong; Fan, Jie; Ju, Weizhu; Ge, Weili; et al.
Abstract : Abstract: The feasibility and safety of intracardiac echocardiography (ICE)-guided catheter ablation for atrial fibrillation (AF) using a minimal/zero-fluoroscopy approach have recently been reported. This approach helps to reduce ionizing radiation exposure and orthopedic complications resulting from using lead aprons. The objectives of this planned prospective, multicenter randomized controlled trial (RCT) (paroxysmal AF (PAF)-ICE trial; ChiCTR2000033624) are to evaluate the efficacy and safety of ICE-guided minimal-fluoroscopy ablation in patients with PAF and the impact on occupational hazards among lab staff. Patients will be randomized in a 1:1 ratio to 2 groups: minimal fluoroscopy group ( n = 216) and traditional approach group ( n = 216). In the minimal fluoroscopy group, an ICE catheter will be used for geometry/anatomic construction, transseptal puncture, catheter tracking, and effusion monitoring. Pulmonary vein isolation (PVI) will be performed using an open-irrigated radiofrequency SmartTouch Surround Flow or SmartTouch catheter (Biosense Webster, Diamond Bar, California, USA), and confirmed by a multipolar Lasso or PentaRay catheter (Biosense Webster). In the traditional approach group, an ICE catheter will not be used. Transseptal puncture will be performed under fluoroscopic guidance, with all geometries constructed by mapping the catheters. The primary efficacy endpoint is freedom from AF recurrence (without antiarrhythmic medications) at 12 months after ablation. Other endpoints include duration of lead apron use, measures of intra-procedural efficiency, and peri-procedural complications. This RCT will evaluate the efficacy and safety of ICE-guided minimal-fluoroscopy ablation in patients with PAF, also evaluate the benefits to lab staff (regarding reducing occupational hazards) related to this "minimal/zero-fluoroscopy" and "leadless" mode.